Associations between the risk of eating disorders, performance level and sport type during adolescence - Sitko, S.; Oviedo-Caro, M. Á.; Mayolas-Pi, C.; Pano-Rodriguez, A.; Munguía-Izquierdo, D.; Moliner-Urdiales, D.; Reverter-Masia, J.; Legaz-Arrese, A. (Journal of Sports Sciences, 2026)
This study examines the risk of eating disorders and psychological maladjustment among adolescent athletes, focusing on gender differences, age effects, and sports participation. A total of 9171 participants aged 11-19 from various performance levels were included in this cross-sectional investigation. Girls showed higher risks of eating disorders and psychological maladjustment than boys, with discrepancies increasing at higher competition levels. All eating disorder domains worsened with age and maturation among girls, while boys showed no significant changes.